Assessing the impact of three feeding stages on rumen bacterial community and physiological characteristics of Japanese Black cattle - Huseong Lee; Minji Kim; Tatsunori Masaki; Kentaro Ikuta; Eiji Iwamoto; Koki Nishihara; Itoko Nonaka; Akane Ashihara; Youlchang Baek; Sungdae Lee; Yoshinobu Uemoto; Satoshi Haga; et al. (Scientific Reports, 2024)
Abstract In Japan, Japanese Black cattle, known for their exceptional meat quality owing to their abundant intramuscular fat, undergo a unique three-stage feeding system with varying concentrate ratios. There is limited research on physiological and rumen microbial changes in Japanese Black cattle during these stages. Therefore, this study aimed to examine Japanese Black steers in these three stages: early (T1, 12–14 months), middle (T2, 15–22 months), and late (T3, 23–30 months). The rumen bacteria of 21 cattle per phase was analyzed using 16S rRNA gene sequencing. Rumen bacterial diversity was significantly higher in T1, with a distinct distribution, than in T2 and T3. Specific phyla and genera were exclusive to each stage, reflecting the shifts in feed composition. Certain genera dominated each stage: T1 had Flexilinea, Streptococcus, Butyrivibrio, Selenomonas, and Kandleria; T2 had Bifidobacterium, Shuttleworthia, and Sharpea; and T3 had Acetitomaculum, Mycoplasma, Atopobium, and Howardella. Correlation analysis revealed significant associations between certain microbial populations and physiological parameters. These findings indicate that changes in energy content and feed composition are associated with physiological and ruminal alterations. This study may guide strategies to improve rumen health and productivity in Japanese Black cattle by modifying diets to specific fattening stages.